Prospects of Biodegradable Polymer (Polyhydroxyalkanoate) production with wastewater - Nayeema, Mehbubun (Brac University, 2020)
This thesis report is submitted in partial fulfilment of the requirement for the degree of Master of Science in Biotechnology, 2019.